Primary malignant melanoma of the esophagus - Chunxiang Ling,; Jizhen Feng,; Jiamei Li,; Qingwei Liu, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Ling C, Feng J, Li J, Liu Q. Primary malignant melanoma of the esophagus. Turk J Gastroenterol 2018; 29: 711-3.